Optics - Ghatak, A. K. (Ajoy K.), 1939- (Tata McGraw-Hill Education, 2012)
"This text provides a comprehensive, balanced account of traditional optics, as well as some of the recent developments in the field. Designed to meet the optics course requirements for undergraduate students of science and engineering, Optics is also an excellent reference source for practicing engineers wanting to obtain a greater understanding of optics."--BOOK JACKET.